A new method for determining the sources of airborne particles. (15th May 2015) - Oteros, J.; García-Mozo, H.; Alcázar, P.; Belmonte, J.; Bermejo, D.; Boi, M.; Cariñanos, P.; Díaz de la Guardia, C.; Fernández-González, D.; González-Minero, F.; Gutiérrez-Bustillo, A.M.; Moreno-Grau, S.; et al.
Abstract: Air quality is a major issue for humans owing to the fact that the content of particles in the atmosphere has multiple implications for life quality, ecosystem dynamics and environment. Scientists are therefore particularly interested in discovering the origin of airborne particles. A new method has been developed to model the relationship between the emission surface and the total amount of airborne particles at a given distance, employing olive pollen and olive groves as examples. A third-degree polynomial relationship between the air particles at a particular point and the distance from the source was observed, signifying that the nearest area to a point is not that which is most correlated with its air features. This work allows the origin of airborne particles to be discovered and could be implemented in different disciplines related to atmospheric aerosol, thus providing a new approach with which to discover the dynamics of airborne particles. Highlights: Concentric Ring Method (CRM) is a method to model the dynamics of airborne particles. We model the distance of airborne particles from emission sources. Most of airborne Olive pollen sources are in the surrounding 209 km.